RCC Immune Microenvironment Subsequent to Targeted Therapy: A Friend or a Foe? - Chen, Wenjin; Pan, Xiuwu; Cui, Xingang (Frontiers in Oncology, 2020)
Renal cell carcinoma (RCC) is composed of different subtypes with distinct molecular and histological tumor heterogeneity. Although the advent of various targeted therapies has improved the survival of patients with advanced RCC over the past 15 years (since 2006), few cases experienced complete response due to drug resistance. Recent studies have demonstrated that the outcomes following targeted therapies are potentially associated with intricate cross-links between immune responses and suppressors in the tumor microenvironment (TME). In addition, progress on drug research and development enhances our awareness and understanding about immunotherapy and combined treatment. In this review article, we intend to make a comprehensive summary about TME and its alterations following targeted therapies, provide valid evidence in this aspect, and discuss optimal matches between targeted therapy and immunotherapy.